Education Expenditure in Aceh Local Governments An Empirical Evidence from Aceh - Aulia Afridzal; Syukriy Abdullah; Hasnawati Hasnawati; Dara Fazella (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims to examine the effect of Local Financial Independence, Last Year Budget Balance, LGs Size, and Local Revenue Growth on Education Expenditure by using data from districts and cities in Aceh for 2011-2015. The results of the study show that the Local Financial Independence and the Previous Budget Fund have a negative effect on the Education Expenditure, while the other two variables have no effect.